Identification and antimicrobial activity of actinomycetes strains isolated from samples in the coastal area of Thanh Hoa – Quang Binh – Quang Tri - Cao Duc Danh; Cao Duc Tuan; Quyen, Vu Thi; Nguyen Mai Anh; Doan Thi Mai Huong; Pham Van Cuong; Chau Van Minh; Minh, Le Thi Hong (Vietnam Journal of Science and Technology, 2018)
In this study, we isolated 46 strains of actinomycetes from 40 samples including: sediments, sponges, soft corals, echinoderms and starfish collected from three sea areas of Vietnam: Thanh Hoa – Quang Binh – Quang Tri. The strains were fermented in A+ medium and fermentation broths were extracted 5 times with ethyl acetate then the extracts were evaporated under reduced pressure to yield crude extracts. Quantitative assay was used to determine MIC (Minimum inhibitory concentration) of extract against 7 reference strains. From the results of screening, we chose 5 strains of actinomycetes that have the highest biological activity (Code: G212, G222, G233, G227 and G241). In particular, strains G222, G233, G227 and G241 were resistant 6/7 strains of microorganisms test, with values MICs from 64µg/ml to 256µg/ml; Moreover, All of the five strains were highly resistant to yeast Candida albicans ATCC10231. These strains were then subjected to morphological and phylogenetic investigations based on 16S rRNA gene sequences. The results showed that strains G212, G222 and G227 belonged to Genus Streptomyces; strains G233 and G241 were identified as Genus Micromonospora.